Letter of Acceptance as a presenter:Understanding the Distress Parents of Hyperactive Children from Attachment Perspective. - Fatahyah, Yahya (Universiti Malaysia Sarawak, UNIMAS, 2014)
Presenter for Understanding the Distress Parents of Hyperactive Children from Attachment Perspective at 1st Malaysia International Counselling Conference 2014(MICC 2014).